Structural characterization of the insecticidal protein from Bacillus thuringiensis. - Choma, Christin Teresa. (University of Ottawa (Canada), 1990)
During sporulation, Baccilus thuringiensis subsp. kurstaki produces a crystalline inclusion body which is toxic upon ingestion by susceptible Lepidopteran larvae. The major component of crystals from Lepidopteran-specific subspecies of B. thuringiensis is a 130-kDa protein, protoxin. Following ingestion by susceptible larvae, protoxin is proteolyzed to yield a 58-70 kDa toxic fragment, toxin. In the present study, a simplified procedure was used for isolating and purifying toxin generated by the tryptic digestion of protoxin from B. thuringiensis subsp. kurstaki HD-73. Characterization of this toxin showed that it is derived from the N-terminal half of the protoxin molecule. The toxin is insoluble at neutral pH values but is moderately soluble at alkaline values above pH 9. Application of several spectroscopic and theoretical procedures to the purified toxin showed that the protein is composed of approximately equal amounts of a $\alpha$-helix, $\beta$-sheet and random coil structures. The tertiary structure of toxin was shown to be comprised of two primary domains; these domains correspond to the toxic and specificity (or binding) domains predicted from analysis of protoxin gene nucleotide sequences. Evidence was obtained that at least one additional domain is present as a structural component of the C-terminal specificity domain. Both the toxic moiety within the protoxin molecule and free toxin were found to be unusually resistant to unfolding by chemical denaturants and to proteolysis. In contrast, the C-terminal half of protoxin could be readily unfolded and was extremely susceptible to proteolytic digestion. The unfolded protoxin and unfolded toxin were shown to refold rapidly into their native and biologically active conformations. Evidence was obtained that the conformation of the toxic moiety of protoxin is very similar to the conformation of toxin. Chemical modification of the cysteine and lysine residues in the protoxin did not affect the biological activity of the protein. However, the introduction of positive, negative or neutral groups onto these residues had a large effect on the solubility of the protein. These results, along with the results obtained from the unfolding/folding, studies, strongly indicate that the primary function of the C-terminal half of the protoxin molecule is to promote the formation of a stable crystal.
Keywords: Biology, Microbiology.